OPERATIONAL EFFICIENCY OR NON-PERFORMING LOANS? ANALYSIS OF SHARIA BANK PERFORMANCE 2015–2022 - Wiyan Mailindra; Sofia Adinda; MHD Rasidin (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
This study aims to analyse the influence of credit and operational risks on banking performance in Islamic commercial banks registered with the Financial Services Authority (OJK) from 2015–2022. Credit risk is measured by the Non-Performing Financing (NPF) ratio. In contrast, operational risk is measured by the Operating Expenses to Operating Income (BOPO) ratio, and banking performance is measured by Return on Assets (ROA). Using the multiple linear regression analysis method, this study found that credit risk (NPF) did not significantly affect ROA. In contrast, operational risk (BOPO) significantly affected ROA—the results of the simultaneous test show that the two independent variables together jeopardise the bank's performance. The coefficient of determination (R²) showed that credit and operational risk could explain 12.2% of the variation in ROA. At the same time, the rest was influenced by other factors not examined in this study. These findings indicate that Islamic bank management needs to focus on managing operational risks to improve efficiency and profitability, although credit risk management is also essential. This study contributes to developing the risk management literature of Islamic banking and suggests further research by considering additional variables.